“PrEP”ing for a PrEP demonstration project: understanding PrEP knowledge and attitudes among cisgender women - Elizabeth C. Pasipanodya; Jamila Stockman; Thupten Phuntsog; Sheldon Morris; Christina Psaros; Raphael Landovitz; K. Rivet Amico; David J. Moore; Jill Blumenthal (BMC Women's Health, 2021)
Abstract Background Prior to implementing a pre-exposure prophylaxis (PrEP) demonstration study, we sought to explore cisgender women’s experiences with HIV prevention, PrEP knowledge and attitudes, and anticipated barriers and facilitators for PrEP uptake and adherence in Southern California. Methods Three focus groups were held with cisgender women of mixed HIV serostatus in San Diego and Los Angeles between November 2015 and January 2016. Women were recruited through local testing sites, community-based organizations, and social media. Focus groups were audio-recorded and transcripts were analyzed using thematic analysis. Results Twenty-two women participated in focus groups, with median age 44 (IQR 30–53) and 6 identifying as non-Hispanic Black, 7 non-Hispanic White, 8 Latina and 1 mixed race. Despite limited prior PrEP knowledge and no PrEP experience, participants expressed interest in taking PrEP. Anticipated benefits were freedom from worry about HIV and control over sexual health; however, these were tempered by concerns including the possibility of increased HIV risk behaviors and potential side effects. Cisgender women reported potential barriers to PrEP uptake and adherence barriers, like competing priorities and poor PrEP access. Conversely, PrEP facilitators included utilizing practical tools such as phone apps and pill boxes as well as receiving encouragement from loved ones and support from other cisgender women on PrEP, women living with HIV and their medical providers. Conclusions Although PrEP awareness was low, participants recognized the importance of PrEP and ways to facilitate adherence. Exploring perspectives of cisgender women is integral to developing effective interventions to support PrEP uptake and adherence for women at elevated risk for HIV.